Competition between Al(III) and Fe(III) for binding onto natural organic matter: In situ monitoring by UV–Vis absorbance spectroscopy. (May 2021) - Xie, Yaping; Guan, Zengfu; Cheng, Jixia; Zhou, Yuxuan; Yan, Mingquan
Abstract: The ubiquitous presence of natural organic matter (NOM) in the aquatic and soil environment significantly affects the transport, fate and bioavailability of Al and Fe elements, NOM itself and other trace metals. In this study, the binding of Al(III) and Fe(III) and their competition for binding onto NOM at varying pH values were monitored in situ via UV–Vis absorbance spectroscopy. It demonstrated that the spectral parameter, e.g., the differential log-transformed absorbance at 400 nm (ΔLnA400 ), can quantify the amount of Al(III) and/or Fe(III) bound onto NOM in all examined cases and will show similar molar extinction coefficients that correspond to the amount of bound Al(III) and Fe(III). Therefore, this approach can not only demonstrate visibly the competition between Al(III) and Fe(III) based on their metal-specific features by evaluating differential absorbance spectra produced by metal binding but can also monitor the reaction kinetics of Al(III) and Fe(III) and their competition for binding onto NOM. To our knowledge, this study is the first to in situ monitor the competition between Al(III) and Fe(III) for binding with NOM quantitatively and at realistic environmental concentrations of both metal ions and NOM. Highlights: Al(III) and Fe(III) bound onto NOM were monitored in-situ by UV–Vis spectroscopy. Spectral index ΔLnA400 can quantify the amount of Al(III) and/or Fe(III) bound onto NOM. ΔLnA400 show similar molar extinction coefficients for Al(III) and Fe(III) binding. Metal-specific spectral features could illustrate the Al(III) and Fe(III) competition. Reaction kinetic of Al(III) and Fe(III) competition is visible through UV–Vis spectra.